A Case Report on Charcot Marie Tooth Disease, and the Role of Vitamin C in this Disease - Waleed, Madeeha Subhan; Sadiq, Waleed (Archives of Clinical and Medical Case Reports, 2020)
Charcot Marie tooth is a heredity disease. There is peripheral nerve demyelination, weakness and impaired motor function. No current medications improve neuropathy in subjects with Charcot-Marie-Tooth disease type 1A. We present to you a case of young Asian male with Charcot Marie tooth showing no improvement with three months treatment with ascorbic acid and folate.